Efficacy of Low-Level Laser Therapy for the Treatment of Nonspecific Chronic Neck Pain: LowLevel Laser Therapy vs. Sham Laser: Low-Level Laser Therapy for Nonspecific Chronic Neck Pain - Momenzadeh, Sirous; Zali, Alireza; Razzaghi, Zahra; Momenzadeh, Fatemeh; Mirkheshti, Alireza; Sayadi, Shahram; Teymourian, Houman; Momenzadeh, Raziyeh (Journal of Lasers in Medical Sciences, 2022)
Introduction: The most common type of neck pain is chronic nonspecific pain. There are conflicting opinions about the beneficial effects of a low-level laser in reducing chronic nonspecific neck pain. The aim of this study was to evaluate the efficacy of low-level laser therapy (LLLT) for the treatment of non-specific chronic neck pain. Methods: This study was conducted as a prospective randomized clinical trial. Forty-four patients were randomly divided into two groups: (1) Intervention group (n=22): LLLT in the red spectra range with a wavelength of 980 (nm) and a power of 16 (J/cm2) was irradiated in the affected areas of the neck, the muscles along the spine, and the upper trapezius; (2) sham group (n=22): A low-level laser was irradiated with a passive probe (non-laser red light) in the affected areas of the neck, the muscles along the spine, and the upper trapezius. The treatment protocol consisted of 12 sessions (15 minutes, three times a week, for four weeks). These patients were evaluated for pain using the visual analog scale (VAS) (0-10). The patients were followed up for four weeks. Results: This study showed a statistically significant reduction in chronic nonspecific neck pain in the LLLT group (P<0.05). Conclusion: It is concluded that LLLT was effective in reducing chronic nonspecific neck pain. LLLT is a non-invasive, safe, and effective method that can improve chronic nonspecific neck pain in patients in the short term